Rake. Series 1 [videorecording (DVD)] - Duncan, Peter, 1964-; Day, Matt, 1971-; Pickering, Adrienne, 1981-; Dykstra, Russell (Acorn Media, 2017)
On any single day, Cleaver Greene is described as many things: to jurors he is hilarious, but to must judges he is an outrage. To the tax office, he is a defendant; to a certain brothel owner, a legend; and to his former cocaine dealer, a tragic loss. His favorite clients are those that appear to be hopelessly guilty. Despite his faults, Greene's wit and charm have won him hordes of female admirers over the years.